Finite element approximation of parabolic hemivariational inequalities - Miettinen, M.; Haslinger, J. (Numerical functional analysis and optimization, 1998)
In this paper we introduce a finite element approximation for a parabolic hemivariational initial boundary value problem. We prove that the approximate problem is solvable and its solutions converge on subsequences to the solutions of the continuous problem